Flood risk management: the role of geo-information in the insurance industry - Guzzetti, Franco; Pasquinelli, Alice (GEOmedia, 2015)
During year 2014 the ABC department of Politecnico di Milano, with the technical support of R3 GIS company, undertook a research project with a major insurance company for the development of a management system aimed to support the underwriting process of flood insurance policies in the consumer market. The scope of the project was the creation of a GIS-based system that allow, on the one hand, to evaluate potential damages related to flood risks assumption and, on the other hand, to support commercial and price strategies in order to balance refund costs and guarantee financial solvency.